2023
DOI: 10.1371/journal.pone.0283105
|View full text |Cite
|
Sign up to set email alerts
|

Inulin alleviates offspring asthma by altering maternal intestinal microbiome composition to increase short-chain fatty acids

Abstract: Technically, symptom of offspring asthma is also closely reliant on its maternal high-fiber diet as well as the intestinal microbiome. Fruits and vegetables are abundant in inulin, and this naturally soluble dietary fiber is endowed with a potential value on offspring asthma control through the maternal intake, but the mechanism now remains less studied. In this study, rats were given with inulin-included drinking water, whereas in normal group rats were allowed with normal water. Afterwards, we analyzed both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The association between maternal gut microbiota and allergic diseases in offspring may also depend on the maternal-fetal transfer of SCFAs, which often changes the composition of the gut microbiota of the offspring at the same time ( 12 , 194 , 195 ). SCFAs are known to have anti-inflammatory properties, and butyrate is able to protect against asthma by inducing FoxP3 on Tregs, suppressing inflammatory Th9 cells and inhibiting IL-13 and IL-5 production by ILC2s ( 207 209 ).…”
Section: Maternal Gut Microbiota: the Role In Offspring Healthmentioning
confidence: 99%
“…The association between maternal gut microbiota and allergic diseases in offspring may also depend on the maternal-fetal transfer of SCFAs, which often changes the composition of the gut microbiota of the offspring at the same time ( 12 , 194 , 195 ). SCFAs are known to have anti-inflammatory properties, and butyrate is able to protect against asthma by inducing FoxP3 on Tregs, suppressing inflammatory Th9 cells and inhibiting IL-13 and IL-5 production by ILC2s ( 207 209 ).…”
Section: Maternal Gut Microbiota: the Role In Offspring Healthmentioning
confidence: 99%
“…For example, IL-4 drives B-2 cells to produce IgE, which fuels allergic reactions . Bifidobacteria , some Clostridia species, and Lactobacillus species can modulate the immune response by producing short-chain fatty acids (SCFAs), such as butyrate, that alter signal transduction to favor tolerance [ 37 ]. Specifically, butyrate acts as a histone deacetylase inhibitor, promoting a more permissive chromatin structure for genes associated with Treg differentiation, such as FOXP3, CD25, CTLA-4, and IL-10.…”
Section: Allergies Asthma and The Microbiomementioning
confidence: 99%
“…However, a recent study by Yuan et al [42] demonstrated that supplementation with inulin, a soluble dietary fiber, significantly altered the composition of maternal gut microbiota by increasing SCFA-producing Bifidobacterium. This supplementation also attenuated the asthmatic inflammatory response in the offspring.…”
Section: Plant-dietary-fiber and Polysaccharide Supplementation In Ma...mentioning
confidence: 99%